The Influence of Audiovisual Media on Postpartum Mothers' Knowledge of the Benefits of Vitamin A at the Ome Inpatient Health Centre - Sarini Kaufua; Tut Rayani Aksohini Wijayanti (Calory Journal Medical Laboratory Journal, 2025)
Postpartum mothers’ understanding of the benefits of vitamin A plays a crucial role in the effectiveness of postpartum vitamin A supplementation programs. Vitamin A contributes to maternal immune function, supports visual health, and enhances the vitamin A content of breast milk, which is essential for infant health. Despite its importance, mothers’ knowledge regarding the benefits of vitamin A during the postpartum period remains inconsistent, indicating the need for more effective health education strategies. One approach that has the potential to improve comprehension among postpartum mothers is the use of audiovisual educational media. This study aimed to examine the effect of audiovisual media on postpartum mothers’ knowledge of the benefits of vitamin A at Ome Inpatient Primary Health Center. A quasi-experimental design with a one-group pretest–posttest approach was employed. The study sample consisted of 30 postpartum mothers selected through purposive sampling. Data were collected using a structured knowledge questionnaire administered before and after the audiovisual education intervention. Data analysis included univariate analysis and bivariate analysis using the paired t-test. The findings demonstrated a statistically significant improvement in postpartum mothers’ knowledge following the audiovisual intervention. Mean knowledge scores increased markedly, accompanied by a shift in knowledge levels from poor and moderate categories to good. Statistical testing confirmed a significant difference between pre-intervention and post-intervention knowledge scores. In conclusion, audiovisual media have a significant positive effect on improving postpartum mothers’ knowledge of the benefits of vitamin A. This educational approach can be considered an effective and practical method for postpartum health education in primary healthcare settings.